2022
DOI: 10.31557/apjcp.2022.23.9.2973
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Surface Dose in the Presence of Unwanted Air Gaps under the Bolus in Postmastectomy Radiation Therapy: A Phantom Dosimetric Study

Abstract: Background:The aim of this study is to design and fabricate a thorax phantom with irregularly shaped trapezoidal slots across the left side of the chest wall, allowing for the creation of unwanted air gaps under the bolus. Method: Surface dose (D surf ) measurements were made with Gaf Chromic EBT3 films at air gaps (0.0, 5.0, 10.0 and 15.0 mm) under gel bolus of thickness (5.0 mm & 10.0 mm), for 3DCRT technique (2 and 3 field) with clinical 6 MV photon beam under uniform and non-uniform air gap condition. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Several studies have suggested that air gaps can affect the dose distribution in the target area, resulting in lower-than-expected doses and decreased uniformity. 19 , 20 However, in this study, the use of SR bolus resulted in a high degree of uniformity in the target area while also meeting clinical requirements for target dosimetry, which may be due to the materials used for the bolus. SR is made using an elastic mold system, which has high flexibility, strong plasticity, resistance to warping and deformation, and low shrinkage.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies have suggested that air gaps can affect the dose distribution in the target area, resulting in lower-than-expected doses and decreased uniformity. 19 , 20 However, in this study, the use of SR bolus resulted in a high degree of uniformity in the target area while also meeting clinical requirements for target dosimetry, which may be due to the materials used for the bolus. SR is made using an elastic mold system, which has high flexibility, strong plasticity, resistance to warping and deformation, and low shrinkage.…”
Section: Discussionmentioning
confidence: 72%
“… 9 Dilson et al studied surface doses when air gap depths varied uniformly between 0 and 15 mm using 3D-CRT technology, showing varying degrees of dose increase on the surface. 28 Butson et al demonstrated that vertical beam incidence on the phantom surface results in a slight decrease in skin dose, with 90% of the maximum dose still passing through a 10-mm air gap between the bolus and skin surface. 7 Benoit et al have proven that air gaps disrupt the electron equilibrium of the radiation beam, potentially affected by factors such as photon energy, air gaps, field size, and bolus thickness, thereby re-establishing dose accumulation in near-surface regions.…”
Section: Discussionmentioning
confidence: 99%